Pentingnya Pendidikan Jasmani Dalam Membantu Perkembangan Fisik Dan Sosial-Emosional Pada Siswa Sekolah Dasar - Anisa Julia Dwi Putri; Keyla Zahra; Nurhalizah Apriyani; Riana Marthalivia Jauhar; Tria Nur Erliani Agustin; Zidna Syifanadia Impian Pragita Mariannisa; Agus Mulyana (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
Physical education in primary schools has an important role in helping children's physical and social-emotional development. Through structured physical activity, students can improve physical fitness, develop motor skills, and understand the importance of a healthy lifestyle. This study aims to examine, describe, and explain the importance of Physical Education in Helping Physical and Social-Emotional Development in Elementary School Students. The research method used is qualitative with literature studies from previous research results. The results showed that physical education has an important role in helping physical and socio-emotional development in elementary school students. Through structured physical activities and social interactions that occur in the context of physical education, students not only improve their physical health but also develop social, emotional, and character skills that are important to achieve success in their future lives.